Synthesis of pH‐responsive isolated soy protein/carboxymethyl chitosan microspheres for sustained pesticide release. Issue 6 (2nd August 2019) - Chen, Long; Zhou, Xinhua; Lin, Guanquan; Chen, Huayao; Hao, Li; Zhou, Hongjun
ABSTRACT: In order to improve the utilization rate of avermectin (AVM), a complex was prepared by electrostatic self‐assembly using isolated soy protein (ISP) and carboxymethyl chitosan (CMCS) for loading AVM to obtain ISP/CMCS@AVM microspheres. The encapsulation efficiency (EE), sustained release property, ultraviolet (UV) protective ability, and toxicity of the microspheres were evaluated, and the release kinetics of AVM from the microsphere at different pHs were investigated. The results demonstrated that the average particle size of ISP/CMCS@AVM was 283.95 nm, and the EE reached 88.42% for AVM after denaturation. After 70 h of exposure to UV light, the residual rate of AVM in ISP/CMCS@AVM was 78.12%, which was significantly higher than 35.18% in the AVM emulsion. Moreover, the formulation imparted pH sensitivity and sustained‐release property to AVM and was consistent with the Korsmeyer–Peppas model, controlled by Fick diffusion. Finally, the insecticidal toxicity of ISP/CMCS@AVM did not differ significantly from that of unmodified AVM. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48358. Abstract :